POLA KETERAMPILAN LITERASI INFORMASI DALAM PROSES PEMBELAJARAN PROBLEM-BASED LEARNING PADA MAHASISWA DI FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Sinurat, Yohana Christy; ", Zulharman; Amtarina, Rina (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTInformation literacy is a key component of lifelong learning and is central to the mission of higher education. Skills required to be information literate require an understanding of: a need for information, the resources available, how to find information, the need to evaluate results, how to work with or exploit results, ethics and responsibility of use how to communicate or share your findings how to manage your findings. Problem-based learning is a learning approach that uses complex problems as a trigger in learning process of students. The aim of this study was to obtain the pattern of information literacy skills in the problem-based learning process in medical students of Riau University. This study uses design of qualitative research with collection of sample with snowball sampling method .Data collection was done by depth interview method. The result of this study shown that informans Informans have the ability of understanding the need of information, have the ability to acces information effectively but haven’t been efficient, and haven’t the ability to evaluate the source of information yet.Keywords: Information Literacy, Problem-Based Learning, Medical Students